Preserving the Most Wonderful World: William H. Hudson in Laura Forchetti's Libro de horas - Maranguello, Carolina (2021)
In 2017 Laura Forchetti published Libro de horas, a collection of poems in which she recovers the figure and work of William Henry Hudson, the English writer who spent his childhood and youth in Argentina and particularized the national landscape based on his singular observation. Considering the special relationship that Hudson established in several of his works between autobiography, naturalistic discourse, and poetic contemplation of nature, the aim of this article will be to consider the contemporary and intimate reception of Hudson and the “Desire” for writing that its reading produces, present in several writers of Argentine literature and that Forchetti figures in a particular way. As will be seen, in a dialogue with his work and with Hudson's childhood memories, her poetry book inquires different scriptural forms (the intimate diary, the herbarium, the medieval Book of Hours, among others) based on gaze’s precarious power; and models, in relation to them, various temporal inflections among which Hudson's diffuse animist religiosity will be fundamental. Finally, opening her writing to the wishes expressed by the English writer in Far Away and Long Ago, she rewrites them, staging his death on the pampas.